29.7k views
5 votes
Apply the distributive property to create an equivalent expression. (6m -7)\cdot 4 =(6m−7)⋅4=

2 Answers

3 votes

Answer:

24m+28

Explanation:

User Luapyad
by
5.6k points
1 vote

Answer:

24m -28

Explanation:

Let A, B and C be any value of function so that;

A(B+C) = AB + AC (Distributive property)

From the formula we can see that A is distributed over B and C.

Given he expression (6m-7)•4

This can also be written as:

4(6m-7)

Distribute 4 over 6m and -7

= 4(6m)+4(-7)

= 24m -4(7)

= 24m -28

Hence the required expression is 24m -28

= 4(6m)

User Alex Argo
by
5.7k points